Do Apixaban Plasma Levels Relate to Bleeding? The Clinical Outcomes and Predictive Factors for Bleeding in Patients with Non-Valvular Atrial Fibrillation - Sutee Limcharoen; Manat Pongchaidecha; Piyarat Pimsi; Sarawuth Limprasert; Juthathip Suphanklang; Weerayuth Saelim; Wichai Santimaleeworagun; Pornwalai Boonmuang (Biomedicines, 2022)
Apixaban can significantly prevent stroke events in patients with non-valvular atrial fibrillation (NVAF), as can be observed from the large, randomized, controlled trial conducted in the present study. However, the real-world evidence of bleeding events related to the apixaban plasma levels in Asian populations is limited. This study aimed to investigate the apixaban plasma levels and clinical outcomes among NVAF patients receiving apixaban, including determining the risk factors associated with bleeding during routine care. Seventy-one patients were included in the study. The median values were 112.79 (5–95th percentiles: 68.69–207.8) μg/L and 185.62 (5–95th percentiles: 124.06–384.34) μg/L for the apixaban trough (Ctrough) and apixaban peak plasma levels (Cpeak), respectively. Stroke and bleeding were found in 8 (11.27%) and 14 patients (19.72%), respectively. There was no statistical significance for Ctrough and Cpeak in the stroke and non-stroke groups, respectively. The median of Ctrough (139.15 μg/L) in patients with bleeding was higher than that in the non-bleeding group (108.14 μg/L), but there was no statistical significance. However, multivariate analyses showed that bleeding history (odds ratio (OR): 17.62; 95% confidence interval (CI): 3.54–176.64; and p-value = 0.002) and Ctrough (OR: 1.01; 95%: CI 1.00–1.03; and p-value = 0.038) were related to bleeding events. Almost all of the patients presented apixaban plasma levels within the expected range. Interestingly, bleeding events were associated with the troughs of the apixaban plasma levels and bleeding history.